Microelectronics, Microsystems and Nanotechnology : Papers Presented at MMN 2000, Athens, Greece, 20-22 November 2000 - Zianni, Xanthi (World Scientific, 2001)
This volume contains papers on the following: CMOS devices and devices based on compound semiconductors; processing; silicon integrated technology and integrated circuit design; quantum physics; nanotechnology; nanodevices, sensors and microsystems. Contemporary news and future challenges in these fields are presented in invited papers.